Efektifitas Pendaftaran Merek Hartlystore.id oleh Usaha Mikro Kecil Menengah (Umkm) di Kota Denpasar - Kadek Bayu Dinata Putra; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Preferensi Hukum, 2022)
This article is motivated by the legal protection of trademarks; the legal protection of trademarks in Indonesia applies after trademark registration is carried out. MSMEs do not have legal protection if the MSME brand has not been registered. This tends to cause potential problems in the future, namely the misuse of brands by irresponsible parties because MSMEs do not have legal protection if the MSME brands have not been registered. Based on the previous explanation, this research aims to discuss the problem of implementing the registration of the hartlystore.id trademark in Denpasar City and what legal consequences will be obtained if the hartlystore.id trademark is not registered. The research method used is empirical legal research, empirical research provides answers to problems related to the reality that occurs in society related to the problems to be studied using a sociological approach, a statutory approach and a fact approach. The main legal source of this research is field research, namely research carried out by going directly into the field to obtain various kinds of data. While the supporting legal sources come from legal books and journals as well as previous research that is relevant to this research. Data collection techniques used are interviews and data observation in the field. From the results of the research, it was found that the implementation of the hartlystore.id trademark registration in Denpasar City had not run effectively this was due to the lack of understanding of MSMEs regarding trademark registration. The legal consequences that arise if the hartlystore.id Mark does not register its trademark, namely the hartlystore.id Mark will not get legal protection from the state if the hartlystore.id mark is imitated or falsified by other parties.